Early onset chilblain lupus erythematosus with atypical presentation in an Indian girl - Puri, Neerja; Alagappan, Anjugam; Brar, Balvinder Kaur (International Journal of Research in Dermatology, 2020)
Chilblain lupus erythematosus (Chilblain LE) is a rare form of lupus erythematosus with only 70 cases reported worldwide with most of the patients in middle age and very few cases in adolescent age group. Herein, we are reporting a 16 years old girl presented with an early age of onset at 10 years with atypical presentation who fulfilled Mayo clinic diagnostic criteria for Chilblain LE.